(untitled) (Research, Society and Development, 2024)
Objective: To evaluate the motor development and other aspects of comprehensive health in a child with sacral agenesis. Methodology: This is a descriptive case report with a quantitative and cross-sectional approach. The instruments used were a sociodemographic evaluation form and the Alberta Scale. This research was submitted to the Research Ethics Committee of UEPB and was approved with the number CAAE: 74237223.1.0000.5187. Results: Child evaluated at 7 months of age. Received the diagnosis of caudal regression syndrome type II, or sacral agenesis, at 5 months. In the physiotherapeutic evaluation, hypotonia and hypotrophy of the lower limbs were observed, as well as delayed DNPM according to the Alberta scale (total score 27, percentile <10). The mother reports irritability, sleep disturbances, and severe constipation. Conclusion: The scientific documentation of rare diseases is important to provide scientific support for professionals who encounter similar cases in their clinical practice. The patient documented through this case report is a child who has various aspects of their health affected by the presence of sacral agenesis, notably motor development, and intestinal function.